2020
DOI: 10.1093/braincomms/fcaa192
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of subtyping methods for neuroimaging studies in Alzheimer’s disease: a call for harmonization

Abstract: Biological subtypes in Alzheimer’s disease, originally identified on neuropathological data, have been translated to in vivo biomarkers such as structural magnetic resonance imaging (sMRI) and positron emission tomography (PET), to disentangle the heterogeneity within Alzheimer’s disease. Although there is methodological variability across studies, comparable characteristics of subtypes are reported at the group level. In this study, we investigated whether group-level similarities translate to individual-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 57 publications
7
60
0
Order By: Relevance
“…Neuroimaging studies have shown topographical conformity and association between tau pathology from tau positron emission tomography (tau-PET) and longitudinal brain atrophy-based neurodegeneration from magnetic resonance imaging (MRI), in cognitively unimpaired individuals [6], prodromal AD and/or AD dementia [4,7,8] and clinical subtypes of AD [9,10]. A critical caveat, however, is the failure to account for heterogeneity in tau-PET topography at a given disease stage (i.e., tau patterns or subtypes) [11][12][13][14][15]. The relationship between tau-PET patterns and atrophy remains unexplored and is important for precision medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging studies have shown topographical conformity and association between tau pathology from tau positron emission tomography (tau-PET) and longitudinal brain atrophy-based neurodegeneration from magnetic resonance imaging (MRI), in cognitively unimpaired individuals [6], prodromal AD and/or AD dementia [4,7,8] and clinical subtypes of AD [9,10]. A critical caveat, however, is the failure to account for heterogeneity in tau-PET topography at a given disease stage (i.e., tau patterns or subtypes) [11][12][13][14][15]. The relationship between tau-PET patterns and atrophy remains unexplored and is important for precision medicine.…”
Section: Introductionmentioning
confidence: 99%
“…We primarily investigated the association between different tau-PET patterns and longitudinal atrophy in the AD continuum (cognitively normal, prodromal AD, AD dementia with Aβ pathology). We secondarily characterized tau-PET patterns on a continuous-scale inspired by the recent conceptual framework [16], compared to and extending beyond the conventional characterization of discrete categorization [13][14][15]17]. We hypothesized that (a) tau-PET patterns would modulate the association between baseline tau-PET and longitudinal atrophy differentially; (b) treating heterogeneity (the different tau-PET patterns) on a continuous-scale over a discretescale could be more appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…We have produced the first comparison of data-driven subtyping results using a disease progression model (SuStaIn) with existing progression-ignorant methods of visual ratings and AVRA. Partial agreement was observed between SuStain and AVRA subtypes on an individual level, and differences may be imputed to the selection of brain regions used to train SuStaIn, that do not cover entirely the same brain region used to assess visual ratings and to a general lack of harmonization of subtyping methods ( Mohanty et al, 2020 ). SuStaIn proved to offer a finer-grained representation of different atrophy patterns as relevant differences in hippocampal volume were observed between subjects from subtypes 1 and 2 that were labeled with minimal atrophy according to the AVRA scores.…”
Section: Discussionmentioning
confidence: 99%
“…In subtype assignments, however, disagreements were considerable. The subtypes therefore need to be further investigated, with an establishment of their harmonization by appropriate methods [ 55 ].…”
Section: Imaging Biomarkers From Ad and Pdmentioning
confidence: 99%